Vibration Analysis of a Two-Step Sine Movable Tooth Drive - Lizhong Xu; Jinan Yang (Shock and Vibration)
In this study, a 3D model of a two-step sine movable tooth drive is developed in the UG software. The finite element model (FEM) analysis package, ANSYS, is used to calculate the natural frequencies and vibration modes of the drive system. The results show that the first twenty natural frequencies can be classified into five families, including the total system vibration mode, single-element vibration mode, two-element vibration mode, three-element vibration mode, and four-element vibration mode. The effects of the system parameters on the natural frequencies and the vibration modes are investigated. The track amplitude, the movable tooth radius, the radius of the movable tooth rotation, and the number of movable teeth affect the natural frequencies and vibration modes of the drive system.